Application of waste heat in a novel trigeneration system integrated with an HCCI engine for power, heat and hydrogen production. (22nd July 2022) - Parsa, Somayeh; Jafarmadar, Samad; Neshat, Elaheh
Abstract: In the current study, biomass was employed as the primary fuel in a multigenerational system to produce power, heat, and hydrogen. Biomass gasification unit, dual fuel homogeneous charge compression ignition (HCCI) engine, Rankine cycle, and waste heat recovery units are the main components of the developed system. The engine exhaust gas contains waste heat which can be utilized for biomass gasification. Hydrogen is the main output of the system whose specific fraction is introduced to the Heptane fueled HCCI engine. The results of the gasification unit and HCCI engine are in good agreement with the experimental reports in the literature. The cold gas and hydrogen efficiencies of the biomass gasification unit were 73% and 34%, respectively. Furthermore, the use of hydrogen as an additional fuel to the heptane-fueled HCCI engine improved the performance of the engine. Except for N O x, other emissions showed a decline. Results indicated that energy efficiency exceeded 57%, while the energy efficiency of the HCCI engine is 38%. Moreover, the exergy efficiency increased from 29% in the single HCCI engine to 47% in the proposed system. Highlights: A novel clean biomass-driven three-generation is proposed. The novel system can produce power, heat and Hydrogen. The cold gas and hydrogen efficiencies are 68% and 32%, respectively.